Evaluation of nutrient content in soils and tea leaves of the lalmonirhat district (Bangladesh Journal of Botany, 2025)
Soil samples from 20 tea gardens of Lalmonirhat district were analysed for physical and chemical properties. The soil texture was mostly loam, while some samples were sandy loam, having 34.59-68.09% sand. Topsoils (0-15 cm depth) were acidic with pH 4.07-6.05, soil organic matter from 0.86-2.00%, and CEC from 3.00-19.00 cmol/kg. The corresponding values for subsoils (15-30 cm depth) were 4.27-5.97, 0.74-1.76% and 8.00-16.40 cmol/kg, respectively. Regarding the nutrient status of soils, the N content ranged from 0.004-0.020%, and available P from 2.99-25.72 mg/kg, K from 3.40-57.31 mg/kg, and S from 13.01-19.85 mg/kg. These values for subsoils were 0.007-0.019%, 1.19-23.57 mg/kg, 2.42-45.62 mg/kg, and 12.78-17.12 mg/kg, respectively. Tea leaves contained 2.63-4.99% N (16.41-31.17% protein), 0.16-0.67% P, 0.16-1.70% K, 0.16-0.33% S, 52.13-108.63 mg/kg Zn, and 187.32-470.07 mg/kg Fe. These results will help to determine the fertilizer requirements for tea gardens in the Lalmonirhat soils.Bangladesh J. Bot. 54(4): 1015-1020, 2025 (December)